(untitled) (American International Journal of Humanities, Arts and Social Sciences, 2020)
This paper investigates the complex developments of identity in contemporary Africa considering that the emergence of identity politics is a consequence of the extraordinarily rapid and profound upheavals and transformations of human society at the turn of the 21st century. Contemporary world has considerably opened up and extraordinarily shrunk in specific historical circumstances. The act of migration particularly, is one that profoundly changes the individual, transforming the relationship of the migrant with his home country and new host country and then impacting their identity as a result. The expanding use of the term, identity politics, is scrutinized in this work and attempts are made at delineating its unwieldy parameters. This in turn reflects the socio-political composition of African societies.